(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2002)
Despite some rather significant differences between various therapeutic models, the necessity for an "encounter" between therapist and client is essential. This article explores the nature of encounter, and pays particular attention to those features or processes that serve to block a meaningful encounter between therapist and client (or any form of human relationship). *That is why I say to any beginner: learn your theories as well as you can, but put them aside when you touch the miracle of the living soul. Not theories but your creative individuality alone must decide.* (Carl Jung, 1928).